(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The Green Agenda has been widely developed in the country’s banking sector. The green finance market is at the initial stage of its formation. The regulator is creating an institutional framework for introducing ESG principles and ensuring sustainable financing according to international standards. This publication shows the prerequisites for a “sustainable” transition, trends associated with current changes in the banking sector, and identifies development prospects.